Myopic consumption and wage increase: The case of Lebanon - Nasser Badra (Arab Economic and Business Journal, 2016)
The paper empirically examines using cointegration analysis consumption's myopic behavior in Lebanon. Empirical results points to the existence of a one-to one long-run relationship between consumption and income over the period 1977-2013. Meanwhile, consumption and income found to be causally independent in the short run. We argue, in the light of our findings, government officials should respond to labor force demands for wage increase only if it does not jeopardize current account deficit path to an unsustainable one. Our main findings is that wage increase could be translated into growth impulses in the long-run given consumption's myopic behavior. Our finding corroborates some previous findings for Lebanon and some emerging markets.
Keywords: 330; Fiscal multiplier; Co-integration; Myopic consumption; Wages; Lebanon